Prevalence and antimicrobial resistance of gram-positive pathogens in Lebanon: The need for surveillance and stewardship - Yara Khachab; Racha Khoumassi; Elie Salem Sokhn (New Microbes and New Infections)
Background: Resistance in Gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE), poses a significant healthcare challenge globally. However, data on these organisms in Lebanon remain limited. This retrospective study aimed to assess the prevalence and antimicrobial resistance patterns of Staphylococcus aureus (S. aureus), coagulase-negative Staphylococci (CoNS), and Enterococcus spp. in clinical infections at the Lebanese Hospital Geitaoui – UMC from 2017 to 2023. Methods: A total of 2676 isolates were collected from urine, blood, respiratory specimens, and other infection sites. Bacterial identification was performed following WHO clinical bacteriology procedures, utilizing gram staining, catalase and coagulase tests, and biochemical assays. Antimicrobial susceptibility testing was conducted using the Kirby-Bauer disk diffusion method and minimum inhibitory concentration (MIC) analysis, interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Statistical analyses were performed using SPSS® version 24, with significance set at p < 0.05. Results: CoNS were the most prevalent (42.83 %), followed by Enterococcus spp. (28.81 %) and S. aureus (28.36 %). Blood cultures had the highest isolation rates (29.04 %), predominantly CoNS (76.45 %). Enterococcus spp. dominated urinary tract infections (85.01 %), while S. aureus was prevalent in wound/surgical site infections (59.23 %). Gender-specific trends showed CoNS and S. aureus more in males, while Enterococcus spp. infections were more common in females. Conclusion: This study provides valuable insights into the prevalence and resistance patterns of Gram-positive pathogens in a Lebanese hospital setting. The findings highlight the need for continuous surveillance and stringent antibiotic stewardship to combat antimicrobial resistance effectively.